(untitled) (Indonesian Librarians’ Journal, 2020)
Introduction. The economic sector plays an important role for Indonesia as a developing country, the government has sought various programs to increase its per capita income by growing various sectors, particularly highlighting the still low portion of national exports of Gross Domestic Product (GDP) of 25 percent. The existence of the Faculty of Economics and Management (FEM) at the Bogor Agricultural Institute will certainly provide input to the government through research and development carried out by lecturers/researchers and students (undergraduate, postgraduate and doctoral programs). To find out and photograph the research carried out by undergraduate students, this research was carried out Methods and Data Collection. The sample is limited to the thesis of the last 5 years (2015-2019) which is taken from the IPB repository. Data analysis. Mapping is reviewed based on the UDC Classification. The table was analyzed descriptively and mapped using VosViewer. Results and Discussion. The number of thesis researches of the Faculty of Economics and Management of IPB during 2015-2019 is 3,145 titles. The most researched topics are “Economic situation, economic policy, economic management, economic planning. Production, services and prices” with a total of 926 research titles, while the least is a topic related to “Insurance” with a total of 6 research titles. The keyword that has the most connectedness is "marketing" with a total of 204 relationships. Keyword analysis using VosViewer is divided into 16 clusters with the largest cluster, namely cluster 1 consisting of 69 keywords and the smallest cluster cluster 12 consisting of 3 keywords. Furthermore, the main supervisor who is most productive in guiding students is Jono Mintarto Munandar (126 guidance). Conclusion. The most popular topics are “Economic situation, economic policy, economic management, economic planning. Production, services and prices” (926 titles). The most common keyword is “marketing” with 205 occurrences. The most productive main supervisor is Jono Mintarto Munandar with a total of 126 students.